Prevalence of Staphylococcus Aureus in Bovine Raw Milk, Antibiogram, and Associated Milking Hygiene Practices Among Small-Scale Farmers in Magu District, Mwanza, Tanzania - Ngassa, Doris Richard (Amref International University, 2024)
Background: Staphylococcus aureus, a common cause of foodborne illnesses, is transmitted from cows to humans through contaminated raw milk, reflecting the milking hygiene standards of the farm. Data on livestock-associated Staphylococcus aureus (LA- S. aureus) in Tanzania's bovine supply chain are scarce. Objective: To assess the prevalence of Staphylococcus aureus in cows’ raw milk, antibiogram, and associated milking hygiene practices among small-scale farmers in the Magu district. Methods: The study employed a cross-sectional design, examining 410 raw milk samples from 48 farmers. Milking hygiene data were collected via questionnaires. Staphylococcus aureus was isolated using standard laboratory methods. Drug susceptibility was tested with the Kirby-Bauer disk diffusion method. Methicillin-resistant Staphylococcus aureus (MRSA) was identified using a cefoxitin disk, with results interpreted according to the Clinical Laboratory Standard Institute Guideline, 2022. Data analysis was conducted using R software, employing descriptive and inferential statistics. Results: The study included predominantly male participants who reared indigenous cattle for dual production. Staphylococcus aureus prevalence was 23.9%, with 16.3% being MRSA displaying varying antibiotic resistance patterns. Penicillin exhibited the highest resistance at 45.9% (45/98), while ciprofloxacin showed the lowest at 1.1% (1/98). Absence of gloves usage (χ2 = 111.7, p < 0.001), poor udder cleaning practices (χ2 = 8.35, p = 0.0154), poor utensil washing practices (χ2 = 10.44, p = 0.0054), hand milking (χ2 = 111.7, p < 0.001), and frequent use of antibiotics (χ2 = 14.06, p = 0.0071) were significantly associated with Staphylococcus aureus contamination in raw milk. Conclusion: The prevalence of Staphylococcus aureus was high with a significant proportion of isolates being MRSA, in raw milk from farmers. High antibiotic resistance underscores the need for improved antimicrobial stewardship. Poor milking hygiene calls for targeted interventions in raw milk production. Recommendation: The veterinary and public health departments should educate farmers on appropriate milking hygiene practices.
Thesis is Submitted to the School of Public Health, Department of Community Health, in Partial Fulfilment oof the Requirements for the Master of Public Health in Applied Epidemiology at Amref International University
Keywords: Staphylococcus Aureus, Milk Hygiene